2009
DOI: 10.1007/s10661-009-1070-y
|View full text |Cite
|
Sign up to set email alerts
|

A game theoretic approach for interbasin water resources allocation considering the water quality issues

Abstract: In this paper, a new game theoretic methodology is developed for interbasin water transfer management with regard to economic, equity, and environmental criteria. The main objective is to supply the competing users in a fair way, while the efficiency and environmental sustainability criteria are satisfied and the utilities of water users are incorporated. Firstly, an optimization model is developed to proportionally allocate water to the competing users in water donor and receiving basins based on their water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…The model employed primarily includes two aspects: one is the objective function, which is designed to allocate water to maximize the economic, social and ecological benefits of different water consumption sectors, and the other is constraint equation which is designed to set up the constraints according to the local resource condition and socio-economic development level [32,33]. In particular, the land use factor was embedded into the model to improve accuracy and practical applicability of the model.…”
Section: Methodsmentioning
confidence: 99%
“…The model employed primarily includes two aspects: one is the objective function, which is designed to allocate water to maximize the economic, social and ecological benefits of different water consumption sectors, and the other is constraint equation which is designed to set up the constraints according to the local resource condition and socio-economic development level [32,33]. In particular, the land use factor was embedded into the model to improve accuracy and practical applicability of the model.…”
Section: Methodsmentioning
confidence: 99%
“…The Shapley value method distributes cooperative benefits according to scientific calculation of the contribution of each member in a cooperation union. Since the Shapley value method has been proved to be highly effective in distributing cooperative benefits [88,92,94,99,100], this paper apply this method to allocate cooperative benefits from electricity utilization.…”
Section: Benefit Allocation Model Of Cooperative Electricity Savingmentioning
confidence: 99%
“…Though the cost gap allocation method [97], the minimum-costs-remaining savings (MCRS) method [98,99], and the core method [100] are often used to allocate benefits among cooperative partners [90,96], the Shapley value method, which allocates benefits among participants based on their contribution to the cooperation, is used in this paper. It has been found to be highly effective.…”
Section: Introductionmentioning
confidence: 99%
“…Grimes-Casey et al (2006, p. 1618 suggested that game theory "allows investigation of the willingness of producers and consumers to seek strategies that promote the common interest of the system while not harming their own interests" when investigating environmental alternatives to disposable bottles. Mahjouri and Ardestani (2010) proposed a game theoretic method for inter-basin water transfer management taking into account economic, equity, and environmental criteria and applying it to a large-scale inter-basin water allocation problem in Iran. Üçler et al (2015) maximized economic benefits of land use and water quality of Namazgah reservoir, Turkey, using a biobjective optimization approach through Game Theory and fuzzy programming.…”
Section: Theoretical Frameworkmentioning
confidence: 99%